A New Real-Time and Guaranteed Lifetime Protocol in Wireless Sensor Networks - Babar Shah; Ki-Il Kim (International Journal of Distributed Sensor Networks)
Real-time applications are time and event critical, therefore they have strict constraint on delay, packet loss, and energy consumption in many wireless sensor networks (WSNs) scenarios, which demands the network to continue QoS operations for a preconfigured lifetime. Due to the scarce energy constraint sensor nodes in WSNs, guaranteed network lifetime is more desirable than unpredictable and uncertain prolonged lifetime. However, in spite of its importance and necessity in WSNs real-time deployment, no research work has been proposed to solve this complex problem. In this paper, we present a new centralized energy and coverage aware node scheduling scheme for WSNs to analyze energy usage as well as balancing energy consumption among nodes to survive for the preconfigured lifetime. Furthermore, the scheduling algorithm is extended to provide real-time routing by adjusting dynamic transmission range according to current energy state of a sensor node. Thus, the energy and coverage aware scheduling with dynamic range forwarding enables the unreliable WSNs to accomplish real-time routing for a guaranteed network lifetime. Simulation results show that the proposed scheme can achieve a 10% increase in real-time packets meeting their deadline and a significantly longer guaranteed network lifetime than protocols reported in the literature.